Evaluating the predictive value of a database of antimicrobial activities of leaf extracts of 537 southern African tree species against six important bacterial and fungal pathogens - Eloff, Jacobus Nicolaas (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2014.